Morning-evening difference of team-handball-related short-term maximal physical performances in female team handball players - Mhenni, T.; Bojsen Michalsik, L.; Mejri, M. A.; Yousfi, N.; Chaouachi, A.; Souissi, N.; Chamari, K. (Journal of Sports Sciences, 2017)
This study investigated the two different time-of-day effect on team-handball-related short-term maximal physical performances. At two different time-of-day, fifteen young female team handball players performed different physical tests: HandGrip (HG) test, Ball-Throwing Velocity (BTV) test, Modified Agility T-test (MAT) and Repeated Shuttle-Sprint and Jump Ability (RSSJA) test. Rating of perceived exertion (RPE) scale was determined following the termination of the last test. Measurements were performed at two separate testing sessions (i.e., in the morning (7:00-8:30 h) and in the early evening (17:00-18:30 h)) in a randomised and counter-balanced setting on non-consecutive days. The results showed that HG (P = 0.0013), BTV (P = 0.0027) and MAT (P < 0.001) performances were better in the evening compared with the morning. During RSSJA, both best and mean sprint times were shorter in the evening compared to the morning (P < 0.001). Moreover, during the latter test, mean jump performance was higher in the evening compared to the morning (P = 0.026). However, there was no morning-evening difference in the best jump performance during RSSJA. Likewise, jump performance decrement was not affected by the time-of-day of testing. On the other hand, RPE fluctuated, with morning nadirs and afternoon/early evening highest values. The findings suggest that in female team handball players, team-handball-related short-term maximal physical performances were better in the afternoon than in the morning.